2013
DOI: 10.1103/physreve.88.032110
|View full text |Cite
|
Sign up to set email alerts
|

Quantum fidelity for degenerate ground states in quantum phase transitions

Abstract: Spontaneous symmetry breaking mechanism in quantum phase transitions manifests the existence of degenerate groundstates in broken symmetry phases. To detect such degenerate groundstates, we introduce a quantum fidelity as an overlap measurement between system groundstates and an arbitrary reference state. This quantum fidelity is shown a multiple bifurcation as an indicator of quantum phase transitions, without knowing any detailed broken symmetry, between a broken symmetry phase and symmetry phases as well as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Since its early development this approach has been applied successfully to a wide variety of systems, ranging from quasi-free Fermions [198,199], the Dicke model [158,161,193,200], matrix product state systems [201], Bose-Hubbard models [202,203], Stoner-Hubbard and BCS models [51]. Various methods have been developed to evaluate the fidelity, such as exact diagonalisation, density matrix renormalisation group [160,204,205], quantum Monte Carlo methods [195,206,207], tensor network algorithms [208,209]. This provides the means to venture into the study of models where analytical solutions are not available [160,204,205,207,210,211].…”
Section: Introductionmentioning
confidence: 99%
“…Since its early development this approach has been applied successfully to a wide variety of systems, ranging from quasi-free Fermions [198,199], the Dicke model [158,161,193,200], matrix product state systems [201], Bose-Hubbard models [202,203], Stoner-Hubbard and BCS models [51]. Various methods have been developed to evaluate the fidelity, such as exact diagonalisation, density matrix renormalisation group [160,204,205], quantum Monte Carlo methods [195,206,207], tensor network algorithms [208,209]. This provides the means to venture into the study of models where analytical solutions are not available [160,204,205,207,210,211].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed [23], spontaneous symmetry breaking leads to a degenerate groundstate for the broken-symmetry phase. Consequently, the relations between the local order parameters calculated from degenerate groundstates are determined by a symmetry group of the system Hamiltonian.…”
Section: Order Parametersmentioning
confidence: 99%
“…For one-dimensional spin lattice systems, doubly degenerate ground states for broken-symmetry phases have been detected by means of the quantum fidelity bifurcations with the tensor network algorithm in various spin lattice models such as the quantum Ising model, spin-1/2 XYX model with transverse magnetic field, among others [20][21][22]. Very recently, Su et al [23] have further demonstrated that the quantum fidelity measured by an arbitrary reference state can detect and identify explicitly all degenerate ground states (N-fold degenerate groundstates) due to spontaneous symmetry breaking in broken-symmetry phases for the infinite matrix product state (iMPS) representation in the one-dimensional (1D) q-state quantum Potts model. It has been also discussed how each order parameter calculated from degenerate ground states transforms under a subgroup of a symmetry group of the Hamiltonian.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For q = 2, 3 and 4 there is a continuous phase transitions at λ = 1, whilst for q = 5 the phase transition is first-order (discontinuous) at λ = 1. Here we remark that the fidelity per site has been demonstrated to be capable of detecting the discontinuous phase transitions in this model through the so-called multiple bifurcation points 31 .…”
Section: Resultsmentioning
confidence: 76%